Impact of pre-charged particles on steady state and pulsed modes of unipolar diffusion chargers. Issue 5 (25th March 2021) - Knoll, M.; Schriefl, M. A.; Nishida, R. T.; Bergmann, A.
Abstract: Fine mode particulate matter (PM) is known to be a major risk for human health as it can cause respiratory and cardiovascular diseases. Whether produced from anthropogenic or natural processes, fine mode PM is often electrically charged with positive, negative and/or bipolar charges. These preexisting charges can, in some cases, significantly affect measurements from sensors which involve a charging stage prior to measurement by, e.g., electrometry. In this work, we demonstrate quantitatively the impact of preexisting charges ( q = 0, ± 1, ± 2 ) on three different unipolar diffusion charging (DC) configurations using both simulations and experiments. The DC configurations include traditional steady state (SS) DC and pulsed modes of DC, where in all configurations a positive corona charger is used. We show that the impact of preexisting charges on SS and modulated precipitation (MP) DC is comparable. Positively pre-charged particles cause a larger deviation for SS and MP DC, in contrast to modulated diffusion charging (MDC), where negatively pre-charged particles have a greater impact. In addition, we show that the ion concentration in the charging region can be increased to significantly reduce the resulting error caused by the pre-charges for both SS DC and MP DC, in contrast to MDC. These results show that the influence of unipolarly pre-charged particles is very differently pronounced for the different modes of DC. The impact strongly depends on the polarity of the pre-charges, characteristics of the charger and the DC configuration itself. These insights are particularly interesting for the design and the application of DC based sensors.